2004
DOI: 10.1007/s15010-004-1037-4
|View full text |Cite
|
Sign up to set email alerts
|

Phlebitis Rate and Time Kinetics of Short Peripheral Intravenous Catheters

Abstract: Linear time kinetics of PIVC phlebitis do not support CDC recommendations for an elective PIVC change after 72 hours, provided daily monitoring of the insertion site occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 14 publications
4
32
1
1
Order By: Relevance
“…Essa incidência, apesar de ser maior que o padrão aceito de 5% pela INS americana, 21 encontra-se próxima àquelas identificadas (20,6% a 27%) em estudos prévios realizados com pacientes adultos. 10,22 A literatura aponta taxas bastante distintas que variam de 2,7% a 54,5%. 4,[7][8][9][10][11][12]23 Essa discrepância pode estar relacionada à dificuldade de padronizar o diagnóstico e às nuances relativas aos graus de flebite, que envolvem sinais como eritema, edema, endurecimento, cordão fibroso, que podem apresentar leituras diferentes aos olhos dos profissionais.…”
Section: Discussionunclassified
“…Essa incidência, apesar de ser maior que o padrão aceito de 5% pela INS americana, 21 encontra-se próxima àquelas identificadas (20,6% a 27%) em estudos prévios realizados com pacientes adultos. 10,22 A literatura aponta taxas bastante distintas que variam de 2,7% a 54,5%. 4,[7][8][9][10][11][12]23 Essa discrepância pode estar relacionada à dificuldade de padronizar o diagnóstico e às nuances relativas aos graus de flebite, que envolvem sinais como eritema, edema, endurecimento, cordão fibroso, que podem apresentar leituras diferentes aos olhos dos profissionais.…”
Section: Discussionunclassified
“…2,12,13 One of the more common organisms associated with PIVC sepsis is Straphylococcusaureusbactaeremia (SAB). SAB is commonly a hospital-acquired infection that is often associated with indwelling medical devices such as PIVCs.…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, a prospective cohort study found in 1,582 patients (2,495 PVC), average rates of phlebitis of 27% [14]. Another prospective observational study in Portugal with older adults (average age of 75.92 years old, SD=14.52) showed that in 1,244 catheters, the incidence of phlebitis was 11.09% [15].…”
Section: Discussionmentioning
confidence: 99%